EVALUATION OF THE POTENTIAL OF FIVE MEDICINAL PLANTS TO INHIBIT ACYL HOMOSERINE LACTONE BASED QUORUM SENSING IN PSEUDOMONAS AERUGINOSA AND ACINETOBACTER BAUMANNII - VIRAJ GALA; NITHYA JOHN; KRUTIKA DESAI (International Journal of Pharma and Bio Sciences, 2013)
Pseudomonas aeruginosa and Acinetobacter baumannii are common nosocomial pathogens, well recognized for their multidrug resistance. Acyl-homoserine lactone (Acyl-HSL) based Quorum sensing (QS) is known to regulate virulence and biofilm maturation in these organisms; hence, inhibition of QS will help to control their pathogenicity. In the study, 5 plants, Rubia cordifolia, Tinospora cordifolia, Picrorhiza kurroa, Cassia fistula and Bauhinia variegata were screened for QS inhibition. A comparison of different extracts from the above plants, for short and long acyl-HSL inhibition in both pathogens, was carried out using reporter strains, Chromobacterium violaceum ATCC12472 and Escherichia coli MG4/pKDT17 respectively. Ethyl acetate extracts of T. cordifolia inhibited short as well as long acyl-HSLs with about 78% & 71% inhibition of long acyl-HSLs in P. aeruginosa and A. baumannii respectively; higher than the positive control, garlic extract (29% and 33% respectively). Further, absence of antibacterial activity of the plant extract confirmed its QS inhibitory potential.